2009
DOI: 10.1111/j.1466-7657.2008.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of childbirth education class: a mixed‐method study

Abstract: This study supports using a mixed-method approach to evaluate client education activity, and highlights the importance of cultivating positive coping measures among the Chinese women after attending childbirth education class when facing childbirth-related anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 22 publications
3
52
0
1
Order By: Relevance
“…Studies that examine the effects of antenatal education on delivery investigated the level of information on delivery (Lee & Holroyd ; Malata et al. ), satisfaction with delivery experience (Spinelli et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examine the effects of antenatal education on delivery investigated the level of information on delivery (Lee & Holroyd ; Malata et al. ), satisfaction with delivery experience (Spinelli et al.…”
Section: Introductionmentioning
confidence: 99%
“…The Program Satisfaction Questionnaires (Lee & Holroyd, 2009) were used to evaluate the process of the program. In order to obtain more information, five open-ended questions were added to ascertain the views of Chinese women on the delivery and content of the program.…”
Section: Methodsmentioning
confidence: 99%
“…The 92 participants completed the Program Satisfaction Questionnaires (Lee & Holroyd, 2009) after the intervention. Only 83 returned the questionnaires, with a response rate of 90.2%.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, studies indicate an imbalance between theory and practice in programs of antenatal classes [54,55]. Research by Piziak and Spinelli et al showed that the level of theoretical knowledge acquired in antenatal classes is usually higher than the ability to use it in practice.…”
Section: School Of Birth -The Idea Aims and Objectivesmentioning
confidence: 99%